Autour des critiques du concept de sexe. Entretien avec Anne Fausto-Sterling - Anne Fausto-Sterling; Priscille Touraille (Genre, Sexualité et Société)
This text is a dialogue between Anne Fausto-Sterling, Professor Emerita of Biology and Gender Studies in the Department of Molecular and Cell Biology and Biochemistry at Brown University, and Priscille Touraille, anthropologist at the CNRS (Centre national de la recherche scientifique) in the department of eco-anthropology and ethnology of the National Museum of Natural History in Paris. It revisits some of the essential issues in the confrontation between the different disciplinary epistemologies of Gender Studies and Biology. Based on the work developed by Fausto-Sterling since the 1990s, the two scholars shift the focus to the problematic articulations between the Social Sciences and Biology that have shaped one of the most important critiques to emerge from Gender studies in the last twenty-five years.